Influence of traffic vehicles against ground fundamental frequency prediction using ambient vibration technique - Kamarudin, A. F.; Md Noh, M. S.; Mokhatar, S. N.; Mohd Anuar, M. A.; Ibrahim, A.; Ibrahim, Z.; Daud, M. E. (2018)
Ambient vibration (AV) technique is widely used nowadays for ground fundamental frequency prediction. This technique is easy, quick, non-destructive, less operator required and reliable result. The input motions of ambient vibration are originally collected from surrounding natural and artificial excitations. But, careful data acquisition controlled must be implemented to reduce the intrusion of short period noise that could imply the quality of frequency prediction of an investigated site. In this study, investigation on the primary noise intrusion under peak (morning, afternoon and evening) and off peak (early morning) traffic flows (only 8 meter from sensor to road shoulder) against the stability and quality of ground fundamental frequency prediction were carried out. None of specific standard is available for AV data acquisition and processing. Thus, some field and processing parameters recommended by previous studies and guideline were considered. Two units of 1 Hz tri-axial seismometer sensor were closely positioned in front of the main entrance Universiti Tun Hussein Onn Malaysia. 15 minutes of recording length were taken during peak and off peak periods of traffic flows. All passing vehicles were counted and grouped into four classes. Three components of ambient vibration time series recorded in the North-South: NS, East-West: EW and vertical: UD directions were automatically computed into Horizontal to Vertical Spectral Ratio (HVSR), by using open source software of GEOPSY for fundamental ground frequency, Fo determination. Single sharp peak pattern of HVSR curves have been obtained at peak frequencies between 1.33 to 1.38 Hz which classified under soft to dense soil classification. Even identical HVSR curves pattern with close frequencies prediction were obtained under both periods of AV measurement, however the total numbers of stable and quality windows selected for HVSR computation were significantly different but both have satisfied the requirement given by SESAME (2004) guideline. Besides, the second peak frequencies from the early morning HVSR curve was clearly indicated between 8.23 to 8.55 Hz at very low amplitude (Ao < 2), but it should be neglected according to the similar guideline criteria. In conclusion, the ground fundamental frequency using HVSR method was successfully determined by 1 Hz seismometer instrument with recommended to specific parameters consideration on field as well as data processing, without disruption from the nearest traffic excitations.